PENGARUH BEBAN KERJA, DISIPLIN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT GUMUH SARI REKREASI KABUPATEN BADUNG - I Nyoman Asna Karmana; Ni Made Dwi Puspitawati; Ni Luh Gede Putu Purnawati (VALUES, 2024)
A company, whether it is government-owned or private, wants maximum achievement related to increasing optimal performance results. This research aims to determine the effect of workload, work discipline and job satisfaction on employee performance. This research was conducted at PT Mitra Krida Mandiri in Badung Regency. The population and sample in this research were employees of PT Gumuh Sari Rekreasi Badung Regency, totaling 40 people as research respondents. The sampling method in this research is the saturated sampling method. Data collection was carried out through documentation, interviews and questionnaire methods. The data analysis technique used in this research is multiple linear regression analysis using the SPSS version 26 program. Based on the results of the analysis, this research shows that workload has a negative and significant effect on employee performance, which means that the more the workload increases, the performance at PT Gumuh Sari Rekreasi Kabupaten Badung will experience a decline. Work discipline has a positive and significant effect on employee performance, which means that the better the work discipline, the performance at PT Gumuh Sari Rekreasi Badung Regency will increase. Job satisfaction has a positive and significant effect on employee performance, which means that the better the job satisfaction, the performance at PT Gumuh Sari Rekreasi Badung Regency will increase.